A Literarture Review: Patient Satisfaction On The Quality Of Nursing Service In The Adult Inpatient Department - Fadhal, Muchtarul; Dioso, Regidor III (Journal of health research and technology, 2025)
Background Patient satisfaction is a vital indicator of healthcare quality, particularly in inpatient settings where nursing care plays a central role. Nurses’ responsiveness, communication, empathy, and technical competence significantly influence patient perceptions, clinical outcomes, and hospital reputation. Understanding what drives satisfaction with nursing care is essential for delivering patient-centered care. Aims This review synthesizes recent global evidence on adult inpatient satisfaction with nursing care, identifies key influencing factors, highlights research gaps, and suggests recommendations for healthcare improvement. Methods A literature review was conducted using PubMed, Google Scholar, and ScienceDirect, guided by the PEO framework. Studies from 2020–2025 involving adult inpatients and measuring satisfaction with nursing care were included if they were in English, primary research, and scored ≥80% on the MMAT. PRISMA guidelines structured the selection process, and data were narratively synthesized. Results Studies from China, Indonesia, Jordan, Ethiopia, Ghana, Finland, Saudi Arabia, Qatar, and South India showed moderate to high patient satisfaction with nursing care. Key determinants included nurse professionalism, communication, empathy, responsiveness, and technical skill. Socio-demographic factors (age, income, education), hospital characteristics (type, staffing), and cultural influences impact satisfaction. Private hospitals and higher socioeconomic groups reported greater satisfaction, while gaps persist in responsiveness and assurance. Failures in nursing care, such as delays and poor communication, were linked to lower satisfaction. Most studies used validated questionnaires, but standardization was lacking. Conclusion Patient satisfaction with nursing care was generally positive but varies by context. Addressing gaps in responsiveness and assurance, ensuring equitable resources, and using standardized, culturally sensitive tools were crucial for improving satisfaction and care quality.